MAPPING OF CURRENTS AND TIDES FOR ANALYSIS OF LOCATION SUITABILITY AND EFFECTIVENESS OF PORT ACTIVITIES, TANJUNG WANGI PORT: - - Kurniasih, Mirna; Dinda Niken Zahra Anandito; Lia Berliana; Lutifiah Apriani; Vanya Chathy Kemala Dewi (Jurnal Ilmu Kelautan SPERMONDE, 2025)
Banyuwangi Regency has 282 km of coastline with high coastal potential to be developed, such as tourism, fisheries, and ports. This study aimed to analyze the suitability of the Tanjung Wangi Port location based on tidal and ocean current data. Tidal data were obtained from the Indonesian Hydrographic Data Center (IHDC), and ocean current data were obtained from AVISO Satellite Altimetry. The data were processed using Microsoft Excel and ArcGIS using the inverse distance weighted (IDW) method to create ocean current maps. The results showed that Tanjung Wangi Port has a double-dominant mixed tidal type. The highest water level was recorded at 5.207 m, and the lowest water level was 0.809 m, with a Mean Sea Level (MSL) of 3.048 m. The sea current speed ranged from 0.023 m/s to 1.414 m/s from the Southeast and Southwest Indian Ocean, with the direction of the sea current towards the Banyuwangi Regency. Stable tidal conditions and low ocean currents make the Tanjung Wangi Port ideal for safe harbor and navigation activities and contribute positively to the effectiveness of port activities. Further research should involve direct field surveys and seasonal variability analyses to improve the accuracy of port planning.